The effects of prostacyclin analogue ZK 36374 and thromboxane synthetase inhibitor UK 38485 on mesenteric ischemia in guinea pigs - (:unkn) unknown (My University, 1990)
The effects of ZK 36374, a prostacyclin analogue and UK 38485, a thromboxane synthetase inhibitor were studied in guinea pigs after performing mesenteric arterial occlusion. In this study, while ZK 36374 significantly lowered the alkaline phosphatase and creatine phosphokinase values two hours after mesenteric arterial occlusion when compared with the control group (p less than 0.005), UK 38485 did not induce any change. In guinea pigs, when given together, ZK 36374 and UK 38485 lowered the enzyme levels to preligation values and the difference was nonsignificant (p greater than 0.1). The histopathologic investigation of the small intestine after giving ZK 36374 and UK 38345 together revealed minimal changes. These findings stress the importance of preserving the PGI2 levels in the PGI2/TXA2 ratio in preventing the increase of lysosomal enzyme levels and histopathologic changes after mesenteric arterial occlusion in guinea pigs.
Keywords: Female; Animals; Male; Drug Evaluation, Preclinical; Alkaline Phosphatase; Imidazoles; Intestine, Small; Iloprost; Mesenteric Vascular Occlusion; Guinea Pigs; Mesenteric Arteries; Creatine Kinase; Thromboxane-A Synthase